Media Digital dan Musik Ibadah Di Gereja Pada Masa Pandemi - Ance Panggabean; Emmi Simangunsong (LPPM Universitas HKBP Nommensen, 2021)
The Covid-19 pandemic has had a tremendous impact not only in Indonesia, but throughout the world. Without exception, the church was affected by its influence. This situation is expected to inspire the millennial generation to keep thinking creatively, and take real action, and to always be a channel of blessing in the midst of the Covid-19 pandemic which may still be prolonged. Young people have played an important role in the history of the Indonesian nation, as well as the church. Including the current millennial generation, who have fluency, flexibility, elaboration and originality in thinking. The use of digital media in worship music in churches during this pandemic is a reflective analysis of the birth of popular culture in the church today ”. This shows that: digital media in church services as a result of the sparks and cultural influences that have long stopped by and been accepted by the church,. However, it is hoped that every Christian has an optimistic attitude and views popular culture from a positive perspective, so that he can accept the positive as an effective media communication for the advancement of church ministry in the future.